Impact of the Four-Hour Rule policy on emergency medical services delays in Australian EDs: a longitudinal cohort study. Issue 12 (15th July 2020) - Man, Nicola Wing Young; Forero, Roberto; Ngo, Hanh; Mountain, David; FitzGerald, Gerard; Toloo, Ghasem (Sam); McCarthy, Sally; Mohsin, Mohammed; Fatovich, Daniel M; Bailey, Paul; Bosley, Emma; Carney, Rosemary; et al.
Abstract : Introduction: Delayed handover of emergency medical services (EMS) patients to EDs is a major issue with hospital crowding considered a primary cause. We explore the impact of the 4-hour rule (the Policy) in Australia, focusing on ambulance and ED delays. Methods: EMS (ambulance), ED and hospital data of adult patients presenting to 14 EDs from 2002 to 2013 in three jurisdictions were linked. Interrupted time series 'Before-and-After' trend analysis was used for assessing the Policy's impact. Random effects meta-regression analysis was examined for associations between ambulance delays and Policy-associated ED intake, throughput and output changes. Results: Before the Policy, the proportion of ED ambulances delayed increased between 1.1% and 1.7% per quarter across jurisdictions. After Policy introduction, Western Australia's increasing trend continued but Queensland decreased by 5.1% per quarter. In New South Wales, ambulance delay decreased 7.1% in the first quarter after Policy introduction. ED intake (triage delay) improved only in New South Wales and Queensland. Each 1% ambulance delay reduction was significantly associated with a 0.91% reduction in triage delay (p=0.014) but not ED length of stay ≤4 hours (p=0.307) or access-block/boarding (p=0.605) suggesting only partial improvement in ambulance delay overall. Conclusion: The Policy was associated with reduced ambulance delays over time in Queensland and only the immediate period in New South Wales. Associations may be due to local jurisdictional initiatives to improve ambulance performance. Strategies to alleviate ambulance delay may need to focus on the ED intake component. These should be re-examined with longer periods of post-Policy data.